The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1007/s40291-014-0110-7
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin Transporter Gene: A New Polymorphism May Affect Response to Antidepressant Treatments in Major Depressive Disorder

Abstract: Our study suggests that rs8076005 in the SLC6A4 gene may be a modulator of antidepressant response, especially when pharmacological treatment is used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…For instance, polymorphisms in the SLC6A4 gene were associated with antidepressant response or remission [28,68,76,81,88,91]. Similar SLC6A4 variants have shown an association with lithium treatment outcomes in patients with BPD [75,102].…”
Section: Lithium Treatment For Bipolar Disordermentioning
confidence: 97%
“…For instance, polymorphisms in the SLC6A4 gene were associated with antidepressant response or remission [28,68,76,81,88,91]. Similar SLC6A4 variants have shown an association with lithium treatment outcomes in patients with BPD [75,102].…”
Section: Lithium Treatment For Bipolar Disordermentioning
confidence: 97%
“…Genetic polymorphisms CREB1 polymorphisms have been associated with mood disorders, mainly exhibiting a significant gender effect (Zubenko et al 2003a(Zubenko et al , 2003bPerlis et al 2007;Dong et al 2009;Utge et al 2010;Juhasz et al 2011;Lazary et al 2011), nevertheless not unequivocally (Burcescu et al 2005;Hettema et al 2009). Findings for CREB1 and antidepressant response are also inconsistent (Murphy et al 2004;Wilkie et al 2007;Serretti et al 2011;Calati et al 2013) and negative findings have also been reported (Dong et al 2009;Crisafulli et al 2012;Matsumoto et al 2014).…”
Section: Cyclic Amp Response Element Binding Proteinmentioning
confidence: 99%
“…Finally, regarding VNS and IPT, few studies have been performed to date. Consequently, the molecular effects of these two important non-pharmacological treatments for MDD patients remain unknown [195][196][197].…”
Section: Molecular Mechanisms Of Non-pharmacological Treatments For Mddmentioning
confidence: 99%